2021
DOI: 10.48550/arxiv.2111.11958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gauge Invariant Description of the $SU(2)$ Higgs model: Ward identities and Renormalization

David Dudal,
Duifje Maria van Egmond,
Igor Figueiredo Justo
et al.

Abstract: The renormalization properties of two local gauge invariant composite operators (O, R a µ ) corresponding, respectively, to the gauge invariant description of the Higgs particle and of the massive gauge vector boson, are analyzed to all orders in perturbation theory by means of the algebraic renormalization in the SU (2) Higgs model, with a single scalar in the fundamental representation, when quantized in the Landau gauge in Euclidean spacetime. The present analysis generalizes earlier results presented in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…But the off-shell properties and interactions of the bound states can in principle deviate at higher orders of the vev [7,9,13,16,17]. Correspondingly, such deviations have been observed for the form factor of the physical vector bosons in lattice simulations [18] and analytically for off-shell Higgs [9,16] and vector boson properties [17]. This can have potentially observable consequences.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…But the off-shell properties and interactions of the bound states can in principle deviate at higher orders of the vev [7,9,13,16,17]. Correspondingly, such deviations have been observed for the form factor of the physical vector bosons in lattice simulations [18] and analytically for off-shell Higgs [9,16] and vector boson properties [17]. This can have potentially observable consequences.…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies showed that higher orders in v can be accounted for analytically [9,14,16,17]. Testing the quality of this, as well as ensuring that no relevant surplus effects beyond this double-expansion arise, requires nonperturbative methods.…”
Section: B Elementary Fields Vs Physical Particlesmentioning
confidence: 99%